Self-Identification in Black, Red, Brown, and White: A clarion call to address medical racism in Native American communities - Boudreaux, Mary (Navigating Academia During COVID-19: Perspectives and Strategies from BIPOC Women, 2023)
This chapter provides a brief autobiographical account of her multiethnic and racial background as a Louisiana Creole in south Louisiana. The author points out that among all racial and ethnic groups in the United States, Indigenous people are the only ones that require some form of lineal Native American descent or blood quantum. The chapter provides an ancestry account of two American Indian tribes along the bayous of south Louisiana, the Chitimacha, and the United Houma Nation. While one federally recognized tribe has attempted to remove all relations to individuals of Black, Negro, or African American descent, the other has closed enrollment to new members (despite lineal descent), with the unifying factor among these communities being establishing progenitors. Finally, the author articulates how lack of access to resources related to issues such as COVID-19 has perpetuated the historical legacy of medical racism in tribal and underserved communities in the United States.
Keywords: COVID-19; Medical racism; Native American; Tribal communities; dept.edl